Sensitivity to BSM effects in the Higgs p T spectrum within SMEFT - Marco Battaglia (SpringerOpen, 2021)
Abstract The study of Higgs boson production at large transverse momentum is one of the new frontiers for the LHC Higgs physics programme. This paper considers boosted Higgs production in the Standard Model Effective Field Theory (SMEFT). We focus on the gluon fusion and t t ¯ $$ \overline{t} $$ H production processes and study the effects of three dimension-6 operators: the top Yukawa operator, the gluon-Higgs effective coupling and the chromomagnetic dipole operator of the top quark. We perform a detailed study of the sensitivity of current and future LHC data to the corresponding Wilson coefficients, consistently accounting for their renormalisation group evolution. We compare the sensitivities obtained with only linear and linear + quadratic terms in the SMEFT by using the spectrum shape and the addition of the Higgs signal yields. We also consider fits of p T spectra in models with heavy-top partners and in MSSM scenarios with a light scalar top and study the validity of the SMEFT assumptions as a function of the new-particle masses and the Higgs p T range. Finally, we extract constraints on the Wilson coefficients for gluon fusion from a simultaneous fit to the ATLAS and CMS data and compare our results with those obtained in global SMEFT analyses.